A semantic study of the conjunction types in Dhakirat al-Jasad and their English translations / Naoual Grine - Naoual , Grine (2017)
This study analyses the conjunction types in Arabic-English novels. The study will focus on using the conjunctions as cohesive ties in the Arabic text “Dhakirat aljasad” and in its English translation “Memory in the Flesh”. The three core objectives that guided this study are: (i) To identify the types of conjunctions used in translating the Arabic novel Dhakirat Aljasad into the English novel Memory in the Flesh. (ii) To look for the similarities and dissimilarities of the semantic features of the Arabic conjunctions in English translations. (iii) To examine the types of shifts in the level of explicitness and shifts in meaning found in the English translation. The theories used to achieve accurate results are: Halliday and Hasan taxonomy of Cohesion (1976) that focus on four semantic types of conjunctions which are additive, adversative, causal and temporal with the Arabic conjunctions. Moreover, the componential analysis by Katz and Fodor (1963) is used in this study to determine the semantic features of the found conjunctions to determine whether the conjunctions used in Arabic and English are similar or dissimilar in meaning. Also, Blum-Kulka’s Shifts of Cohesions (1986) theory used to examine the types of shifts in the level of explicitness and text meaning occurred during the translation process. The data derived from the excerpts of both novels are collected and analysed thoroughly;and its finding clearly reveals that the Arabic and English conjunctions are mostly related, sometimes overlapped and rarely different. More than that, the results also show that some Arabic conjunctions considered as prepositions, adverbs, and pronouns in English tend to create explicit shifts in the translated text.